PEMANFAATAN NUMERICAL WEATHER PREDICTION DAN CITRA SATELIT HIMAWARI-9 DALAM ANALISIS KONDISI ATMOSFER SAAT HUJAN LEBAT: (Studi Kasus 14 Maret 2024) - Rafi, Rayhan; Syahid, Wisnu; Kaizzi Larasati, Kanaya; Aydin Umardani, Syarif Abdillah; Abigael, Febby Debora; Kristianto, Aries (JTIK (Jurnal Teknik Informatika Kaputama), 2025)
Heavy rainfall occurred in the Special Region of Yogyakarta on March 14, 2024. This rainfall event was categorized as extreme weather, as data from the Regional Disaster Management Agency (BPBD) reported damage in 496 affected locations. Heavy rainfall can occur due to atmospheric instability caused by the growth of convective clouds (cumulonimbus). The phenomenon of heavy rainfall was monitored using remote sensing systems in the form of satellites to observe and analyze the event. Yogyakarta's topography explains the use of ECMWF ERA-5 model data to identify wind distribution patterns (streamlines) influenced by westerly winds. The Convective Cloud Overlay (CCO), red-green-blue (RGB), and High-resolution Cloud Analysis Information (HCAI) methods were applied to interpret cumulonimbus cloud development, observed from the formation phase (08:00 UTC) to the dissipation phase (18:00 UTC). Observations indicated a decrease in cloud-top temperature to -80°C at 09:00 UTC, followed by dissipation with a temperature of -20°C at 18:00 UTC. Atmospheric instability indices were analyzed using numerical weather prediction (NWP) methods to obtain quantitative values for indices contributing to heavy rainfall, such as SSI, LI, KI, TT, SWEAT, and CAPE. This study concluded that a "moderate" increase in instability index values explained why convective cloud development occurred.